2017
DOI: 10.1002/qj.3183
|View full text |Cite
|
Sign up to set email alerts
|

On the interaction of observation and prior error correlations in data assimilation

Abstract: The importance of prior error correlations in data assimilation has long been known; however, observation-error correlations have typically been neglected. Recent progress has been made in estimating and accounting for observation-error correlations, allowing for the optimal use of denser observations. Given this progress, it is now timely to ask how prior and observation-error correlations interact and how this affects the value of the observations in the analysis. Addressing this question is essential to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 50 publications
(101 reference statements)
4
64
0
Order By: Relevance
“…In this study we use the "nearest wet pixel" approach described in García-Pintado et al (2013). The mapping in the nearest wet pixel approach is dependent on the inundation status at the model location.…”
Section: Model and Data Assimilationmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study we use the "nearest wet pixel" approach described in García-Pintado et al (2013). The mapping in the nearest wet pixel approach is dependent on the inundation status at the model location.…”
Section: Model and Data Assimilationmentioning
confidence: 99%
“…There have been recent advances in real-time 2-D hydrodynamic modelling and the acquisition and processing of relevant remote sensing observations (earth observations, EOs) (Raclot, 2006;Andreadis et al, 2007;Schumann et al, 2007Schumann et al, , 2011Mason et al, 2010aMason et al, , 2012aMason et al, , 2014. Consequently, several studies have shown the benefit of applying DA to operational flood forecasting (Durand et al, 2008(Durand et al, , 2014Montanari et al, 2009;Roux and Dartus, 2008;Neal et al, 2009;Matgen et al, 2010;Mason et al, 2010b;Giustarini et al, 2011;García-Pintado et al, 2013, 2015. Grimaldi et al (2016) review the potential of EOs for inundation mapping and water level estimation and their use for calibration, validation and constraint of real-time hydraulic flood forecasting models.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As in Fowler et al . () and Simonin et al . (), the analysis error STD is reduced when increasing the density of assimilated observations by retrieving some of the small‐scale information that is lost when thinning the observations.…”
Section: Resultsmentioning
confidence: 99%